Catastrophic Health Expenditure Estimates: A Methodological Evaluation and Policy Implication - Edy-Ewoh, Uduakobong; Adesoye, A. B.; Tella, S. A. (NIU Journal of Social Sciences, 2019)
Evidence-based studies that produce the incidence of catastrophic health expenditure (CHE) and household impoverishment are often used to assess a health system performance and its impact on the well-being of the people. These evidenced-based studies offer rich sources of materials for policy makers to aid the development of policies that will ensure the optimal performance of the health systems. Literature however alludes that the incidence of CHE and household impoverishment are sensitive to the methodology used in their assessment. This poses a challenge as the level of incidence computed may be understated thus undermining urgent policy intervention.  Using the same set of data, this study examined the extent to which the incidence of CHE and household impoverishment are responsive to different methodologies - with particular emphasis on how the definitions and operationalisation of variables affect their values. The study arrived at a difference of 53.42% and 21.80% in the incidence of CHE and Household impoverishment respectively due to differences in the definition and operationalisation of variables. The percentage of poor households increased by 20.57% as the definition of household necessity increased beyond food. Since the results showed wide differences in values computed, the study recommended the need to standardize the system of assessing the incidence of CHE and household impoverishment in Nigeria as a result of consuming health care to ensure comparable results that will ease policy making relating to healthcare financing in Nigeria. Keywords: Catastrophic Health Expenditure, Impoverishment, Methodology, Policy intervention, Nigeria